A Static Dynamic in African Politics - Siphamandla Zondi (African Journal of Political Science)
Political developments in Africa continue to manifest that disjuncture between progress and stalemate. There continues to be a co-existence between change and stasis in many areas of African society. This is a sort of static dynamism where great hope inspired such developments as citizens electing new governments in countries like Malawi and Zambia, only to encounter deliberating despair marked by the destruction of Somalia by a ravaging terror-linked and externally driven conflict in the form of drones and bombings, the stubborn growth of terror in Mozambique, terror in the Sahel deepening. The incidence of political corruption put into the spotlight by the South African commissioning probing the so-called state capture, and the extradition of a former Mozambican finance minister for trial in the U.S. adds the gloom that threatens to dim hopes.